Resiliensi Pada Siswa Kelas 3 SMK: Keterkaitan antara Self-Control dan Rasa Bangga - Agustiningsih, Rika Dwi; Silvianis Diwanti, Yusrinda; Husnaini, Rovi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Third-grade vocational high school students had high academic demands and also faced lots of new experiences and challenges between school, extracurricular activities, and social life. It raised negative emotions that are sometimes uncontrollable so that affected student’s ability to complete their academic assignments well. In this situation, students were expected to build resilience, selfcontrol, and positive emotions which will make them more likely to succeed. The aim of the present research was to determine the relationship of self-control and pride with resilience in the third-grade vocational high school students. The research sample consisted of 177 who were selected through the cluster random sampling method. To collect data, resilience scale, self-control scale, and achievement emotions scale were used. The results showed that pride was the positive emotion that affected student resilience the most. Also, pride and self-control are positively related (r=04.76). By using multiple linear regression analysis, the prediction of the effect of these variables on the resilience can be obtained. The values of the multivariable determination coefficient was 0.610, indicating that at least 61% variation on the resilience was determined by combination of self-control and pride. The results that increase of self-control and encourage of pride become more resilience leads to more success causes they allow to learn and grow in all situations. KEYWORDS: resilience; self-control; pride, students, vocational high school